MeerKAT: a journey from commissioning to science - Hugo, Benjamin Vorster (Rhodes University, Faculty of Science, Department of Physics and Electronics)
This dissertation presents a collection of work completed for the South African Radio Astronomy Observatory in characterizing calibrator fields PKS B1934-638, PKS B0407-65 and 3C286, the development of a facet-based multi-direction peeling scheme for the CUBICAL calibration framework and incorporation into an end-to-end containerized data reduction framework, a study of a transitional millisecond pulsar candidate, and characterization of baseline dependent archiving tooling for MeerKAT. Our long term studies of PKS B1934-638, PKS B0407-65 indicate that these bandpass and flux calibrators are stable over multiple years. We also find that, especially at low frequencies in the UHF band, the population of sources surrounding these stellar Gigahertz Peaked Sources (GPS) can contribute to errors two to three orders of magnitude above desired bandpass calibration solution stability, if left unmodeled. We derive new new full sky models of these fields, currently in use by the MeerKAT Science Data Processor. We characterize the MeerKAT feed alignment using the refraction-driven linearly polarized thermal light from the Moon in order to derive a new model for the linear polarization of the stable quasar 3C286 down to 544 MHz. Part of this work includes characterization of ionospheric corrections using the International Global Navigation Satelite System Service and direct measurement of total electron content above the MeerKAT site using interchange data from the South African TrigNET service. We find that current commonly-employed techniques achieve corrections to ionospheric Faraday rotation no better than 1 rad mô€€€2. This is the main limitation on the accuracy of polarimetric observation using the MeerKAT array. We find that 3C286 intrinsically depolarizes at frequencies below 1 GHz, with an associated non-linear increase in the intrinsic source rotation measure. We present an improvement to workflows using the CUBICAL calibration framework, developed at Rhodes University. Modern radio interferometers presents a significant challenge to calibrate, often necessitating memory and computeintensive direction-dependent calibration towards many directions in order to improve the fidelity of radio images in order to meet scientific goals. We developed a framework to simplify the model prediction aspect of these direction-dependent calibration workflows using targeted faceting. Using our scheme users use models derived from the DDFACET imaging package and only need to provide lattices to mark regions of sky to which direction-dependent calibration solutions need to be solved for. This simplifies a laborious multi-step process in traditional calibration packages that need to be executed per direction. The approach is compared to an image-space corrective regime and incorporated into the VERMEERKAT end-to-end calibration framework for MeerKAT data. The improved direction-dependent calibration techniques were then applied in an analysis of the transitional millisecond pulsar candidate CXOU J110926.4-650224. The link between accreting binary systems (where emission is dominated by the synchrotron emission of relativistic jets from thermo-nuclear reaction onto the Neutron Star surface by the infalling matter) and binary radio pulsars is currently elusive. This is due to the lack of a large population of such transitional systems "” only three confirmed transitional systems are known at the time of writing. It is thought that infalling matter effectively quenches the radio pulsar mechanism. Our candidate was found to be variable in the optical and the X-ray, with transitions between low, high and flaring states lasting anywhere from a tens of seconds to tens of minutes, seen in archival observations spanning nearly three decades. For the first time we detect low level synchrotron emission (_ 50 mJy beamô€€€1) coincident with this system using MeerKAT, including a flare within minutes of a flare detected in X-ray using the XMM-Newton observatory. Our analysis indicate that there is no clear anti-correlated behaviour between radio and X-ray state transitions in this system, unlike other candidate systems"”indicating that such transitional systems may not exhibit homogenous behaviour. This suggests that the processes driving the X-ray mode-switching in this system are not directly linked to the processes responsible for emitting radio synchrotron radiation. Finally, we consider the problem of MeerKAT data archiving. We present a qualification analysis, using MeerKAT data, of the Rhodes University baseline-dependent archiving package XOVA, which can be used to compress and archive MeerKAT data in interchange standard-compliant format. The data rates from interferometric array radio telescopes, such as MeerKAT, grow as the square of the number of antennas in such an array. For the sake of reproducibility and future reanalysis it is important to archive calibrated visibility products. The degree to which calibrated visibility products can be compressed, by averaging, depends on the amount of smearing that can be tolerated at a fixed distance from the center of the images synthesized from these visibility products. This is, traditionally, set by the longest spacing in the interferometric array, with all other spacings averaged to the same integration and channelization as the longest spacing. We find that, using baseline-dependent averaging techniques "“ where averaging intervals are set per interferometric spacing "“ we can achieve space savings an order of magnitude better than traditional averaging approaches, with no appreciable loss of image fidelity when compared to traditional averaging approaches.
Keywords: MeerKAT; Interferometry; Ionosphere; Pulsars